RESEARCH ON THE DEVELOPMENT OF A LIQUID EXTRACT BASED ON FRESH AND DRY FLOWERS OF ROBINIA PSEUDOACACIA - Aleksandrova, Oleksandra; Tanina, Mariia (SWorld-Ger Conference proceedings, 2024)
Experimental work is devoted to the study of the influence of extraction conditions (the state of raw materials and the concentration of the extractant) on the process of extracting polyphenolic compounds from the flowers of Robinia Pseudoacacia. Determin